2005
DOI: 10.1158/1078-0432.ccr-04-1832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Information in Prostate Cancer with the Help of a Small Set of Hypermethylated Gene Loci

Abstract: Purpose: Our study was designed to evaluate promoter CpG island hypermethylation in the diagnosis and prognosis of prostate cancer. Experimental Design: Primary prostate cancers from 53 patients, pelvic lymph nodes, noncancerous prostate tissues, and prostate cell lines were analyzed. Real-time methylation-specific PCR was used to identify CpG island hypermethylation at five promising gene loci (i.e., GSTP1, APC, PTGS2, MDR1, and RASSF1a). Results: At three gene loci (GSTP1, APC, and PTGS1) and CpG island, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 51 publications
3
95
0
Order By: Relevance
“…In addition, we found that APC methylation level was significantly higher in tumor tissues of stage pT3 or above (24.0%), compared with those with tumor stage pT2 (12.3%). However, Bastian et al (2005) did not find a link between GSTP1 or APC methylation and tumor progressive markers using methylation-specific PCR to measure DNA methylation.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, we found that APC methylation level was significantly higher in tumor tissues of stage pT3 or above (24.0%), compared with those with tumor stage pT2 (12.3%). However, Bastian et al (2005) did not find a link between GSTP1 or APC methylation and tumor progressive markers using methylation-specific PCR to measure DNA methylation.…”
Section: Discussionmentioning
confidence: 85%
“…4,5 To date, aberrant hypermethylation of CpG island-containing promoters has been identified at numerous loci in PCa, including GSTP1 and APC. [7][8][9][10][11] However, relatively limited studies have used the quantitative PSQ method to explore DNA hypermethylation status of various genes in PCa. 5,6 In the earlier studies using multiple genes by the PSQ method, it was demonstrated that both APC and GSTP1 methylation levels were significantly higher in PCa samples than in control samples.…”
Section: Figure 1 Methylation Level Of (A) Adenomatous Polyposis Colmentioning
confidence: 99%
“…7,8,10,11 Although it is typically relatively high in PCa and low in BPH, the reported strength of the association varies widely between studies. 7,8,10,11 As previously mentioned, the inconsistency in methylation results for these genes may be due to differences in detection methods, regions of interest, and/or tissue types. In the present study, the combination of APC and GSTP1 methylation by a quantitative method yielded a sensitivity of 92.8% while maintaining a specificity of 100% for the discrimination of PCa samples from benign prostate samples.…”
Section: Figure 1 Methylation Level Of (A) Adenomatous Polyposis Colmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of two or more methylated genes even increased diagnostic accuracy (e.g. ''GSTP1 and PTGS2'': sensitivity and specificity to 96-100%) [8,9]. Moreover, CGI hypermethylation in PCA tissue has prognostic relevance and correlates with pathological stage [8][9][10], tumor grade [8][9][10][11] and disease progression [8].…”
Section: Introductionmentioning
confidence: 99%